Is Burglary A Violent Crime? An Empirical Investigation Of Classifying Burglary As A Violent Felony And Its Statutory Implications - Kopp, Phillip (2014)
Under the common law, burglary is defined as a crime committed against the property of another, and is listed as a property offense for purposes of statistical description by the Uniform Crime Reports (UCR) and the National Crime Victimization Survey (NCVS). However, burglary is prosecuted and sentenced as a violent crime under habitual offender laws at the federal level, and can be regarded as violent in state law, depending on varied circumstances. Using a mixed methods approach, the current study compared state and federal burglary and habitual offender statutes to an empirical description of the offense. First, a comprehensive content analysis of the provisions of state burglary and habitual offender statutes showed that burglary is often treated as a violent crime, instead of prosecuting and punishing it as a property crime and then separately charging and punishing any violent acts that occasionally co-occur with it. Second, using data from the period1998-2007 from the NCVS and the National Incident Based Reporting System (NIBRS), results showed that in contrast to its statutory classification, burglary is overwhelmingly a non-violent offense. The reported incidence of actual violence or threats of violence during a burglary ranged from a low of 0.9% in rural and suburban areas, to a high of 7.6% in highly urban areas. Additionally, a victim was present during only 26% of all burglaries. These findings led the present study to recommend reform for state and federal burglary and habitual offender statutes to comport with the empirical description of the burglary characteristics provided. Furthermore, it is suggested that federal law should be amended to remove non-violent burglaries as a violent felony under habitual offender statutes, and instead, that burglary should be prosecuted and punished at a level equal with other non-violent property crimes, unless actual violence occurred during the offense